Type I vs. quasi-type II modulation in CdSe@CdS tetrapods: ramifications for noble metal tipping. Issue 43 (20th October 2017) - Pavlopoulos, Nicholas G.; Dubose, Jeffrey T.; Liu, Yawei; Huang, Xing; Pinna, Nicola; Willinger, Marc-Georg; Lian, Tianquan; Char, Kookheon; Pyun, Jeffrey
Abstract : We report on noble metal tipping of heterostructured nanocrystals (NCs) of CdSe@CdS tetrapods (TPs) as a chemical reaction to manifest energetic differences between type I and quasi-type II heterojunctions. Abstract : We report on noble metal tipping of heterostructured nanocrystals (NCs) of CdSe@CdS tetrapods (TPs) as a chemical reaction to manifest energetic differences between type I and quasi-type II heterojunctions. The energetics between zincblende (ZB) CdSe seed and wurtzite CdS TP arms has previously been probed primarily using ultrafast spectroscopic methods. However, to interrogate the energetics of CdSe@CdS TPs from both larger and very small ZB CdSe seeds ( i.e., effective diameters ( D eff ) 6.2 to 1.8 nm) we utilize the photodeposition of gold nanoparticles as a facile and selective chemical reaction to correlate reaction rates with tetrapod energetics. We observe a 20-fold enhancement in the rate of selective photodeposition of a single AuNP tip onto this series of TPs, which were attributed to straddling of type I vs. quasi-type II energetics as a direct consequence of varying ZB CdSe seed size. Synthetic access to type I and quasi-type II TPs enabled the synthesis of singly tipped AuNP-CdSe@CdS TPs in gram quantities, which is the largest scale synthesis of metal–semiconductor Janus nanoparticles to date.